Determination of Catechin Diastereomers from the Leaves of Byrsonima species Using Chiral HPLC-PAD-CD - Rinaldo, Daniel [UNESP]; Batista, Joao M. [UNESP]; Rodrigues, Juliana [UNESP]; Benfatti, Ana C. [UNESP]; Rodrigues, Clenilson M. [UNESP]; Santos, Lourdes Campaner dos [UNESP]; Furlan, Maysa [UNESP]; Vilegas, Wagner [UNESP] (Wiley-liss, 2010)
When catechins are found in plant extracts, they are almost always identified as catechin and/or epicatechin probably due to stereoselectivity of the enzymes involved in the biosynthesis of these substances. However, the lack of reports regarding to ent-catechin as well as ent-epicatechin does not necessarily mean that these compounds have not been produced. In fact, most of the previous reports used chromatographic conditions not suitable for such separation. This article describes a simple and reliable analytical HPLC-PAD-CD method for simultaneous determination of catechin diastereomers both in infusions and extracts from the leaves of Byrsonima species. The direct separation of catechin, ent-catechin, epicatechin, and ent-epicatechin was obtained in normal phase by HPLC-PAD-CD using Chiralcel OD-H as chiral stationary phase and n-hexane/ethanol with 0.1% of TFA as mobile phase. Chirality 22: 726-733, 2010. (C) 2010 Wiley-Liss, Inc.
Keywords: chiral chromatography; enantioseparation; circular dichroism; plant extract